BREM: A Distributed Blogger Reputation Evaluation Model Based on Opinion Analysis - Weng, Y.; Hu, C.; Zhang, X. (Informatica)
BREM: A Distributed Blogger Reputation Evaluation Model Based on Opinion Analysis